SoTL and STEM: A review of The Scholarship of Teaching and Learning: A Guide for Scientists, Engineers and Mathematicians - Abrahamson, Earle Derek (Teaching and Learning Inquiry, 2019)
A review of The Scholarship of Teaching and Learning: A Guide for Scientists, Engineers, and Mathematicians by Jacqueline M. Dewar, Curtis D. Bennett, and Matthew A. Fisher, Oxford University Press, 2018.